Analisis Strategi Layanan Purna Jual Motor Honda dalam Meningkatkan Minat Beli pada PT. Bina Eka Sahada Trading Jatimulyo Lampung Selatan - Amalia, Putri; Amir, Aprilianto; Gunawan (Prodi Administrasi Bisnis FISIP Universitas Tulang Bawang Lampung, 2025)
After-sales service is a service provided by a company after a customer purchases a product or service. After-sales service is one of the supporting factors in increasing people's buying interest in Honda motorbikes. PT. Bina Eka Sahada Trading Jatimulyo is a company operating in the automotive trading sector, and is an official Honda motorbike dealer with one of the largest sales in Lampung. This research aims to analyze the after-sales service strategy for Honda motorbikes implemented by PT. Bina Eka Sahada Trading Jatimulyo in increasing consumer buying interest. This research uses qualitative methods with data obtained through in-depth interviews with management, after-sales service staff, and consumers who have used Honda motorbike products. The research results show that an after-sales service strategy which includes a guarantee provided, availability of spare parts, adequate service and facilities can increase consumer satisfaction which has an impact on consumer buying interest in Honda motorbike products. Keywords: strategy, after sales service, purchase interest